Listening to Africa"s children in the process of practical theological interpretation: A South African application - Swart, Ignatius (HTS teologiese studies, 2012)
As part of the theological task of developing a publicly oriented ministry that will do justice to the social plight of children in Africa, this article adopted as its point of departure an appreciation of the new ‘hermeneutics of listening’ that is advanced today by an interdisciplinary movement of scholars from the disciplines of practical theology, theological ethics and religion studies. Emphasising the fact that this new hermeneutics is by and large the result of this scholarly movement’s newly-found engagement with, and exposure to, the social science field of childhood studies, the article moved from a more general appreciation of the new hermeneutical line of thinking to a more pertinent evaluation of the unfolding of this line of thinking in the scholarly context of Africa. In a further development that narrows the African focus to South Africa, the results from a recent empirical investigation amongst members of the South African practical theological academy were discussed in particular to determine the extent of this group’s shift to the new line of thinking. This led the article to make a concluding statement, in the light of its overt practical theological interest, about the way in which the new ‘hermeneutics of listening’ to children could still be seen as an important ongoing challenge, not only for practical theological scholarship in South Africa but also within the larger context of Africa.